2013
DOI: 10.1016/j.foodchem.2013.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Monola oil versus canola oil as a fish oil replacer in rainbow trout feeds: Effects on growth, fatty acid metabolism and final eating quality

Abstract: Monola oil, a high oleic acid canola cultivar, and canola oil were evaluated as replacers of fish oil at three levels of inclusion (60%, 75% and 90%) in rainbow trout diets. After a 27-week grow-out cycle, the diet-induced effects on growth, fatty acid metabolism and final eating quality were assessed. Overall, no effects were noted for growth, feed utilisation or fish biometry, and the fatty acid composition of fish fillets mirrored that of the diets. Dietary treatments affected fillet lipid oxidation (free m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 52 publications
4
19
0
2
Order By: Relevance
“…Both total fat and total fatty acid ADC of the different experimental diets were high (90.5-96.7%), which is in accordance with authors reporting similar results with diets including rapeseed as a FO replacer in rainbow trout (Caballero et al, 2002;Martins et al, 2006;Turchini et al, 2013). This replacement could even increase lipid digestibility at low water temperatures in salmonid species (Caballero et al, 2002;Karalazos et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Both total fat and total fatty acid ADC of the different experimental diets were high (90.5-96.7%), which is in accordance with authors reporting similar results with diets including rapeseed as a FO replacer in rainbow trout (Caballero et al, 2002;Martins et al, 2006;Turchini et al, 2013). This replacement could even increase lipid digestibility at low water temperatures in salmonid species (Caballero et al, 2002;Karalazos et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Final weights of fish fed the experimental single rapeseed oil diets were all high, which is in agreement with many studies in salmonids (Bell et al, 2003;Huang et al, 2008;Pettersson et al, 2009;Turchini et al, 2013). Also, values of FCR and SGR were similar to those obtained in studies including different levels of rapeseed oil in salmonid diets (Caballero et al, 2002;Turchini et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is known that number of goblet cells in many species increases toward the rectum and this may be explained by further need for lubrication in this region (Murray et al, 1996;Khojasteh, Sheikhzadeh, Mohammadnejad, & Azami, 2009). It has been reported that CO as a fish oil alternative has no adverse effects on growth, feed utilization, biometry and FA composition in rainbow trout (Turchini et al, 2013). Finally, it has been suggested that total replacement of fish oil by vegetable oils does not induce adverse changes in fish growth and performance (Benitez-Dorta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the obvious effects in fillet fatty acids, also the total volatile compounds and sensory properties, namely, the appearance, odour, flavour, and texture of fillet, can be affected [8][9][10][11][12][13][14]. In particular, in cases of sweet-water fish species, the recorded impacts included reduction of the total amount of aldehydes and alcohols concomitant to fillet n-3 fatty acids reduction, increase of n-6 derived aldehydes, and related sensory-perceived "off-flavour" for plant oil fed fish [9,10,15].…”
Section: Introductionmentioning
confidence: 99%